2018
DOI: 10.1016/j.burns.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Children with severe burns display no sex differences in exercise capacity at hospital discharge or adaptation after exercise rehabilitation training

Abstract: The burn injury does not have sex-dependent effects on LBM or exercise capacity in severely burn injured children. Differences in relative peak VO and peak HR suggest the need for burn specific exercise programs for improving the efficacy of a rehabilitation program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Many research reports [3][4][5] have lamented a worrisome situation in poor countries where high cases (up to 90%) of burns injuries are recorded with high percentage rate of mortality and was attributed to lack of social awareness programs related to prevention and safety measures, while most of the cost-effective and safety measures are practically implemented in high income countries [1]. In general, studies [6,7] have shown that about 265,000 deaths are reported every year, as such burns have become eminent health concern globally.…”
Section: Introductionmentioning
confidence: 99%
“…Many research reports [3][4][5] have lamented a worrisome situation in poor countries where high cases (up to 90%) of burns injuries are recorded with high percentage rate of mortality and was attributed to lack of social awareness programs related to prevention and safety measures, while most of the cost-effective and safety measures are practically implemented in high income countries [1]. In general, studies [6,7] have shown that about 265,000 deaths are reported every year, as such burns have become eminent health concern globally.…”
Section: Introductionmentioning
confidence: 99%
“…The negative situation in those countries was attributed to lack of social awareness programs related to prevention and safety measures, while most of the cost-effective and safety measures are practically implemented in high income countries [5]. In general, studies [6,7] have shown that about 265,000 deaths are reported every year, as such burns have become eminent health concern globally. Assessment of burn injury clinically by experience personnel via visual observation is very subjective and totally dependent on the experience of the personnel with recorded high accuracy of approximately 75% [8], in addition of been painful due to invasive nature (blanching).…”
Section: Introductionmentioning
confidence: 99%
“…Prior assessment of exercise capacity with the Steep Ramp Test (SRT) predicted exercise capacity 6 months after discharge, and can therefore be used to identify "at risk" patients at an early stage. Until now, all longitudinal studies on exercise capacity during the first year after pediatric burns were performed by the research group of the Shriners Hospital for Children in Galveston, U.S.A. [6,[14][15][16][17][18][22][23][24][25][26][27]. It is hard to make a fair comparison between these studies and our findings, as the Galveston patients suffered from more extensive burns compared to our participants (>30% or >40% versus <35% TBSA burned, respectively).…”
Section: Discussionmentioning
confidence: 68%
“…These studies included children and adolescents with extensive burns (>30% or >40% of total body surface area (TBSA)). In this exceptional group of patients, exercise capacity was shown to be affected up to 5 years post-burn, despite significant improvements caused by structured exercise and/or drug interventions [14][15][16]20,21,[24][25][26][27]. Fortunately, such extensive pediatric burns are rare in both the Netherlands and the U.S.A. [28], and this will also be the case in other developed countries.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation